Triple Bottom Line - A Step Ahead on the Way of Corporate Social Responsibility - Sachdeva, Rekha (Prabandhan: Indian Journal of Management, 2010)
The role of corporates by and large has been understood in terms of a commercial business paradigm of thinking that focuses purely on economic parameters of success. As corporates have been regarded as institutions that cater to the market demand by providing products and services, and have the onus for creating wealth and jobs, their market position has traditionally been a function of financial performance and profitability. However, over the past few years, as a consequence of rising globalisation and pressing ecological issues, the perception of the role of corporates in the broader societal context within which it operates, has been altered. Stakeholders (employees, community, suppliers and shareholders) today are redefining the role of corporates taking into account the corporates’ broader responsibility towards society and environment, beyond economic performance, and are evaluating whether they are conducting their role in an ethical and socially responsible manner. As a result of this shift (from purely economic to ’economic with an added social dimension’), many forums, institutions and corporates are endorsing the term Corporate Social Responsibility (CSR).